Chemical Preservatives Action on Microbial Growth in a Model System of Refrigerated Prepeeled Potatoes - Giannuzzi, Leda (1993)
The effect of different concentrations of citric acid and ascorbic acid (applied individually or in mixture's) on microbial growth in potato homogenate was analyzed and compared to the sodium bisulfite action during storage at 4°C in low gaseous permeability films. These experiments allowed one to simulate the behavior of prepeeled potatoes but with a known amount of added preservative to evaluate additive or synergic effects. Total viable microorganisms, Enterobacteriaceae , Pseudomonas sp., Lactobacillus sp., molds, yeasts, Clostridium sulfite reducers, psychrotropic microorganisms, and aerobic and anaerobic viable spores were analyzed during storage time. Inhibition indexes produced by the tested preservatives were calculated for the different microorganisms. Sodium bisulfite solutions (100 ppm) had no inhibitory effect. Concentrations of 3,500 ppm citric acid and 10,000 ppm ascorbic acid showed antimicrobial action as well as mixtures of citric acid/ascorbic acid of the following compositions (in terms of total acids concentration): 2,700/2,000, 3,500/2,000, and 2,700/3,000 ppm. A higher effect on Enterobacteriaceae was observed in comparison with other microorganisms. The apparent synergic effect of these acids when they were applied together was demonstrated to be actually an additive effect when concentrations of undissociated acid in the mixtures were considered instead of total concentration.